Tergal and pleural wing‐related tissues in the German cockroach and their implication to the evolutionary origin of insect wings. Issue 2 (27th January 2021) - Clark‐Hachtel, Courtney; Fernandez‐Nicolas, Ana; Belles, Xavier; Tomoyasu, Yoshinori
Abstract: The acquisition of wings has facilitated the massive evolutionary success of pterygotes (winged insects), which now make up nearly three‐quarters of described metazoans. However, our understanding of how this crucial structure has evolved remains quite elusive. Historically, two ideas have dominated in the wing origin debate, one placing the origin in the dorsal body wall (tergum) and the other in the lateral pleural plates and the branching structures associated with these plates. Through studying wing‐related tissues in the wingless segments (such as wing serial homologs) of the beetle, Tribolium castaneum, we obtained several crucial pieces of evidence that support a third idea, the dual origin hypothesis, which proposes that wings evolved from a combination of tergal and pleural tissues. Here, we extended our analysis outside of the beetle lineage and sought to identify wing‐related tissues from the wingless segments of the cockroach, Blattella germanica . Through detailed functional and expression analyses for a critical wing gene, vestigial ( vg ), along with re‐evaluating the homeotic transformation of a wingless segment induced by an improved RNA interference protocol, we demonstrate that B. germanica possesses two distinct tissues in their wingless segments, one with tergal and one with pleural nature, that might be evolutionarily related to wings. This outcome appears to parallel the reports from other insects, which may further support a dual origin of insect wings. However, we also identified a vg ‐independent tissue that contributes to wing formation upon homeotic transformation, as well as vg ‐dependent tissues that do not appear to participate in wing formation, in B. germanica, indicating a more complex evolutionary history of the tissues that contributed to the emergence of insect wings. Abstract : Research Highlights: Diverse types of wing‐related tissues identified in cockroaches provide new insight into the complex evolutionary history of the tissues that contributed to the emergence of insect wings, a chief example of morphological novelty.